Could education promote the Israeli-Palestinian peace process? - Mayssun El-Attar (Centre for Microdata Methods and Practice (cemmap), 2010)
The goal of this paper is to measure Palestinians' attitudes towards a peace process and their determinants. One novelty is to define these attitudes as multidimensional and to measure them carefully using a flexible item response model. Results show that education, on which previous evidence appears contradictory, has a positive effect on attitudes towards concessions but a negative effect on attitudes towards reconciliation. This could occur if more educated people, who currently have very low returns to education, have more to gain from peace but are less willing to reconcile because of resentment acquired due to their experience.
Keywords: I20; O15; O53; 330; conflict resolution; education; latent attitudes; item response models; Konflikt; Bürgerkrieg; Bildungsinvestition; Palästina; Israel